On the right and left of the centre: ABET and ECE postgraduate educational research in South Africa, 1995–2004 - Rule, P (South African Journal of Higher Education, 2011)
Adult Basic Education and Training (ABET) and Early Childhood Education (ECE) are the stepchildren of the South African education system in terms of resource allocation and public attention, and yet vitally inform the enterprise of lifelong learning and the prospects for developing a learning nation. The paucity of research on ECE and ABET, and Adult Education more widely, in the Project for Postgraduate Educational Research (PPER) survey, underlines this marginality. Drawing on theoretical perspectives from lifelong learning and lifelong education, this article examines the trends within the existing corpus of research in ECE and ABET regarding regional and institutional profile, methodology and thematic focus in the decade 1995–2004. It also considers the relation between key policy developments and the research corpus. It argues that the development of ECE and ABET depends in part on extending and deepening research capabilities in both areas in South African universities. This is a tenuous prospect given the marginality of the two areas in relation to schooling and the current neoliberal context of tertiary education.